Palladium-Catalyzed Allylic Alkylations as Versatile Tool for Amino Acid and Peptide Modifications - Kazmaier, Uli; Bayer, Anton; Deska, Jan (Synthesis, 2013)
Palladium-catalyzed allylic alkylations are especially suitable for the introduction of γ,δ-unsaturated side chains into amino acids and even peptides. Glycine ester enolates are generally used as nucleophiles in these reactions, they react at a very low temperature (–78 °C) to give the products of isomerization-free allylation. In reactions of cis-configured allylic substrates, the olefin geometry can be transferred to the product. Because the syn position of the corresponding syn/anti π-allyl complex formed in this case is more reactive, this isomerization-free protocol also allows regioselective and stereoselective allylations. Using stannylated allylic substrates gives metalated amino acid derivatives that are ideal substrates for subsequent Stille couplings or tin–iodine exchange reactions. If peptides are deprotonated with excess strong base, the corresponding ester or amide enolates formed can also be subjected to allylation; in this case the stereochemical outcome can be controlled by the peptide chain.
Keywords: allylic alkylations; amino acids; enolates; peptides; peptide modifications; palladium